Forests and farming in Tanzania - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
A unique forested area survives on the Usambara mountains of north-eastern Tanzania. These forests have been isolated from the Guinea-Congo rainforests for a very long period and, as a result, 25-30% of plant species are endemic to the area. The...